Tell Me What You Believe and I'll Tell You What You Want: Empirical Evidence for Discriminating Value Patterns of Five Types of Religiosity - Fontaine, Johnny R. J. (The international journal for the psychology of religion, 2000)
On the basis of Wulff's (1997) theoretical model of religious attitudes and of Schwartz's (1992; Schwartz & Huismans, 1995) value theory, a refined theoretical framework has been constructed and empirically tested concerning the relation between 5 types of religiosity and personal value orientation. Two theoretical value patterns associated with religiosity were identified: A theological one focused on transcendence and mutual care, and a sociopsychological one focused on acceptance of social order and avoidance of uncertainty. Religious commitment and Hutsebaut's (1996) types of religious attitudes, which are based on Wulff's theoretical model, were, in a theoretically predicted and meaningful way, empirically related to a different value pattern. Moreover, each observed pattern could be explained as a specific combination of the 2 theoretically derived value patterns.